Réponses

2014-07-21T14:23:33+02:00
Bonjour 

on a C= 144x -4x^3/x^3+12x^2+36x  alors pour x = 6

C= 144 × 6 - 4 × 6^3 / 6^3 + 12 × 6^2 + 36 × 6
C= 864 - 4 × 216 / 216 + 12 × 36 + 36 × 6 
C= 864 - 864 / 216 + 12 × 36 + 36 × 6
C= 0/ 216 + 12 × 36 + 36 × 6
C=0

on a C= 144x -4x^3/x^3+12x^2+36x  alors pour x = 0,01

C= 144 × 0,01 - 4 × 0,01^3 / 0,01^3 + 12 × 0,01^2 + 36 × 0,01
C= 1,44 - 4 × 0,000001 / 0,000001 + 12 × 0,0001 + 0,36
C= 1,44 -  0,000004 / 0,000001 + 0,0012 + 0,36
C= 1,439996 / 0,361201 
C≈ 3,987

Ca serait plus clair avec des parenthèses...